Industry analysis of PT. Mayora Indah, Tbk. (Case Study). - Indradi, Dimas Ariowibowo; Ningsih, Ayu; Rufaidah, Popy (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2023)
This study aimed to examine forces that determined the strategic position of PT. Mayora Indah Tbk competes in the Indonesian food and beverage industry by using the modified Porter's five forces model. This model assists in analyzing the industry based on the positioning of the companies strategically based on the strength of industry stakeholders, competition between existing companies, bargaining power over buyers and suppliers, the threat of new entrants and substitute products or services, and the forces from other stakeholders. This research employed the case study method, focusing on a particular case requiring careful observation and analysis. The results indicated that the food and beverage industry relied on a company's ability to maintain a substantial competitive advantage and business profitability in the Indonesian food and beverage industry. Hence, the company could preserve its position in the market and have the opportunity to continue its growth in the future. This study combines Porter’s five forces and financial analysis as the case study in external factors industry analysis of PT Mayora Indah Tbk. Porter's forces analysis revealed that PT Mayora had a solid and quite profitable competitive advantage in Indonesia's food and beverage industry. Therefore, the company could maintain its position in the market and have the opportunity to continue growing